Edukasi Digital Marketing dan Pembayaran Cashless sebagai Upaya Pengembangan UMKM di Desa Pisangan Jaya - Nugroho, Mochamad Eko; Arosanto, Eka Sahari; Arisandi, Yossy; Purnomo, Hendro; Saryono, Anto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program, the Community Service Program (KKN), was implemented to address the low digital literacy of MSMEs in Pisangan Jaya Village, RT 02 RW 014, Sepatan District, Tangerang Regency. This lack of understanding of digital marketing, the use of online platforms, and the implementation of cashless payments hinders local MSMEs' growth and market expansion. This activity aims to increase the capacity of MSMEs to utilize digital technology, specifically through digital marketing education, optimization of WhatsApp Business, Google Business Profile, and the use of QRIS-based payment systems. Implementation methods included field observation, coordination with village officials, material development, hands-on application use, and outreach on the theme "Strengthening MSMEs Based on Technology." The results of the activity demonstrated an increased understanding of participants regarding digital promotion strategies, content creation, the convenience of cashless transactions, and the importance of digital financial records. This program helps MSMEs better prepare for competition through the use of modern technology and has a positive impact on local economic development.